Yield performance and stability analysis of promising soybean genotypes under contrasting environments in the semi-arid zone of Sudan - Ngalamu, T.; Bulli, P.; Meseka, S.K. (Agricultural Research Communication Center, 2023)
Background: The challenge to food security posed by climate change and coupled with the substantial rise in the global population, necessitate a shift in crop improvement programmes towards developing crop cultivars with stable and high yield potentials across a wide range of agro-ecological conditions.